Arthur family papers - Arthur, Chester Alan, 1864-1937.; Arthur, Chester Alan, 1901-1972.
Chiefly papers of the son and grandson of U.S. president Chester Alan Arthur, Chester Alan Arthur, Jr. (1864-1937), sportsman and rancher, and Chester Alan ("Gavin") Arthur III (1901-1972), author and bohemian, consisting of correspondence, diaries, scrapbooks, writings, printed material, and clippings. Correspondents include Herbert Agar, Upton Sinclair, and Alan Watts.
Papers of Chester Alan Arthur, Jr., chiefly 1874-1937, relate to his travels abroad and in the United States and to his interest in clubs, cookery, horses, hunting, and the Trinchera Estate, his 250,000 acre ranch in Costilla County, Colo. Papers of Chester Alan Arthur III, chiefly 1900-1972, relate to the Irish republican movement, his founding of the magazine Dune Forum, his work with the Utopian Society of America, and his interest in poetry, free-lance writing, astrology, the occult, and sexology. Includes manuscript of his book, The Circle of Sex (1962), and of an unfinished biographical study of the Arthur family.
Other persons represented include Chester Alan Arthur, Jr.'s wife, Myra Fithian Andrews Arthur; her son by her first marriage, Loring Andrews; President Arthur's brother and sister, William A. Arthur and Malvina Arthur Haynesworth; and other members of the Andrews, Arthur, and Fithian families.
Library of Congress Prints and Photographs Division.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Agar, Herbert, -- 1897-1980 -- Correspondence; Andrews, Loring; Arthur, Chester Alan, -- 1829-1886 -- Family; Arthur, Myra Fithian Andrews, -- 1870-1935.; Arthur, William A., -- approximately 1833-; Haynesworth, Malvina Ann Arthur, -- 1832-1916.; Sinclair, Upton, -- 1878-1968 -- Correspondence; Watts, Alan, -- 1915-1973 -- Correspondence; Andrews family; Arthur family; Fithian family; Utopian Society of America; Dune Forum; American periodicals; Astrology; Bohemianism; Clubs; Cooking; Horses; Hunting; Occultism; Poetry; Ranches -- Colorado -- Costilla County; Republicanism -- Ireland -- History -- 20th century; Sexology -- Research; Europe -- Description and travel; Ireland -- Politics and government -- 20th century; Trinchera Ranch (Colo.); United States -- Description and travel